Disruption of a Structurally Important Extracellular Element in the Glycine Receptor Leads to Decreased Synaptic Integration and Signaling Resulting in Severe Startle Disease - Schaefer, Natascha; Berger, Alexandra; van Brederode, Johannes; Zheng, Fang; Zhang, Yan; Leacock, Sophie; Littau, Laura; Jablonka, Sibylle; Malhotra, Sony; Topf, Maya; Winter, Friederike; Davydova, Daria; et al. (The Journal of Neuroscience, 2017)
Functional impairments or trafficking defects of inhibitory glycine receptors (GlyRs) have been linked to human hyperekplexia/startle disease and autism spectrum disorders. We found that a lack of synaptic integration of GlyRs, together with disrupted receptor function, is responsible for a lethal startle phenotype in a novel spontaneous mouse mutantshaky, caused by a missense mutation, Q177K, located in the extracellular β8-β9 loop of the GlyR α1 subunit. Recently, structural data provided evidence that the flexibility of the β8-β9 loop is crucial for conformational transitions during opening and closing of the ion channel and represents a novel allosteric binding site in Cys-loop receptors. We identified the underlying neuropathological mechanisms in male and femaleshakymice through a combination of protein biochemistry, immunocytochemistry, and bothin vivoand invitroelectrophysiology. Increased expression of the mutant GlyR α1Q177Ksubunitin vivowas not sufficient to compensate for a decrease in synaptic integration of α1Q177Kβ GlyRs. The remaining synaptic heteromeric α1Q177Kβ GlyRs had decreased current amplitudes with significantly faster decay times. This functional disruption reveals an important role for the GlyR α1 subunit β8-β9 loop in initiating rearrangements within the extracellular-transmembrane GlyR interface and that this structural element is vital for inhibitory GlyR function, signaling, and synaptic clustering.SIGNIFICANCE STATEMENTGlyR dysfunction underlies neuromotor deficits in startle disease and autism spectrum disorders. We describe an extracellular GlyR α1 subunit mutation (Q177K) in a novel mouse startle disease mutantshakyStructural data suggest that during signal transduction, large transitions of the β8-β9 loop occur in response to neurotransmitter binding. Disruption of the β8-β9 loop by the Q177K mutation results in a disruption of hydrogen bonds between Q177 and the ligand-binding residue R65. Functionally, the Q177K change resulted in decreased current amplitudes, altered desensitization decay time constants, and reduced GlyR clustering and synaptic strength. The GlyR β8-β9 loop is therefore an essential regulator of conformational rearrangements during ion channel opening and closing.
EVALuna2:33340